RESEARCH OF SERVICE SYSTEMS WITH CYCLIC WAITING TIME - Koba, E. V.; Mikhalevich , K. V. (Problems of Informatization and Management, 2021)
We study queuing systems with cyclic waiting times for claims Gl / G / 1 and SM / SM / I, in which the time spent by claims in the orbit has a general non-lattice distribution, and the service discipline FCFS is adopted. Conditions for the ergodicity of the embedded Markov chain are derived. The results of statistical modeling are presented.